2019
DOI: 10.1093/brain/awz191
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Mendelian mutations in a large UK population-based Parkinson’s disease study

Abstract: Our objective was to define the prevalence and clinical features of genetic Parkinson’s disease in a large UK population-based cohort, the largest multicentre prospective clinico-genetic incident study in the world. We collected demographic data, Movement Disorder Society Unified Parkinson’s Disease Rating Scale scores, and Montreal Cognitive Assessment scores. We analysed mutations in PRKN (parkin), PINK1, LRRK2 and SNCA in relation to age at symptom onset, family history and clinical features. Of the 2262 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
59
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 108 publications
7
59
2
1
Order By: Relevance
“…However, whole‐gene multiplications had been more frequently detected than the single‐nucleotide variants (SNVs). It has been reported that multiplications of SNCA are observed in around 0.05% of European PD patient populations . Other genes related to hereditary forms of PD have copy number variations (CNVs) demonstrating the role of loss of function .…”
mentioning
confidence: 99%
“…However, whole‐gene multiplications had been more frequently detected than the single‐nucleotide variants (SNVs). It has been reported that multiplications of SNCA are observed in around 0.05% of European PD patient populations . Other genes related to hereditary forms of PD have copy number variations (CNVs) demonstrating the role of loss of function .…”
mentioning
confidence: 99%
“…Der Anteil der Patienten mit monogenetischen Formen aufgrund bekannter Mutationen wird auf bis zu 10% geschätzt [31], kann aber in Abhängigkeit der Population selbst für eine spezifische Mutation, z.B. G2019 S-Mutation im LRRK2-Gen, bis zu 30% betragen [32].…”
Section: Genetische Stratifizierung Als Konzept (Monogenetisch Bis Gwas)unclassified
“…Other causative autosomal dominant LRRK2 mutations (e.g., involving substitution of Arginine at position 1,441 with cysteine, glycine, or histidine) appear to be rare worldwide, with the exception of the R1441G mutation underlying a large proportion of familial PD cases in the Spanish Basque population [4,9]. Only 2 Asian cases of R1441C PARK-LRRK2 have been reported previously [10][11][12][13][14], and further study is needed as many under-represented populations have not been tested [6,15,16].…”
Section: Introductionmentioning
confidence: 99%